XSLT 2.0 and XPath 2.0 : programmer's reference - Kay, Michael (Wrox programmer to programmer, 2008)
Combining coverage of both XSLT 2.0 and XPath 2.0, this book is the definitive reference to the final recommendation status versions of both specifications. The authors start by covering the concepts in XSLT and XPath, and then delve into elements, operators, expressions with syntax, usage, and examples. Some of the specific topics covered include XSLT processing model, stylesheet structure, serialization, extensibility, and many others. In addition to online content that includes error codes, the book also has case studies you'll find applicable to your own challenges.